(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Carbon-based nanomaterials, including carbon nanotubes, carbon nanofibers, active carbon, and graphene, have shown great potential for environmental remediation. They can be used for the removal of various pollutants from water and soil, making them valuable for environmental protection. Research has focused on their effectiveness in eliminating contaminants, their eco-safety, and sustainability. These nanomaterials are being explored for the remediation of organic and inorganic pollutants from wastewater, as well as for water treatment. Their unique advantages, such as high earth-abundance, recyclability, and low-cost production processes, make them promising for addressing environmental challenges. The use of carbon-based nanomaterials in environmental remediation is a rapidly evolving field, with a growing body of research supporting their potential applications.